2016
DOI: 10.1016/j.neuroimage.2015.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Different coupling modes mediate cortical cross-frequency interactions

Abstract: Cross-frequency coupling (CFC) has been suggested to constitute a highly flexible mechanism for cortical information gating and processing, giving rise to conscious perception and various higher cognitive functions in humans. In particular, it might provide an elegant tool for information integration across several spatiotemporal scales within nested or coupled neuronal networks. However, it is currently unknown whether low-frequency (theta/alpha) or high-frequency gamma oscillations orchestrate cross-frequenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 43 publications
2
57
0
Order By: Relevance
“…Notably, there is an ongoing debate about whether the low frequency phase drives the amplitude of the high frequency component or vice versa [77]. It has been suggested that both components could drive the interaction to facilitate information integration across temporal scales [78], but it is unclear how directional synchrony across several spatiotemporal scales is established.…”
Section: Multiplexed Cognition and Its Spatiotemporal Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, there is an ongoing debate about whether the low frequency phase drives the amplitude of the high frequency component or vice versa [77]. It has been suggested that both components could drive the interaction to facilitate information integration across temporal scales [78], but it is unclear how directional synchrony across several spatiotemporal scales is established.…”
Section: Multiplexed Cognition and Its Spatiotemporal Organizationmentioning
confidence: 99%
“…Furthermore, amplitude correlations [57,60] might exhibit similar characteristics and could be applied to both connectivity and CFC analyses [78] and could serve as a useful control analysis [60]. The mutual information framework provides a promising approach to capture non-linear dependencies in electrophysiological data 2 ([122], Figure Id), which cannot be described by linear correlation analyses.…”
Section: Figurementioning
confidence: 99%
“…Local field potential (LFP) oscillations in local networks result from the synchronization of neuronal activity, and the synchrony of oscillations from separate areas of the brain may contribute to the temporal binding of information [3][4][5][6][7]. Synchronous oscillations in sensorimotor areas reflect coordinated firing of activity across regions and may contribute to optimally planned and executed movements [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The cerebellum plays a pivotal role in many aspects of sensorimotor processing and displays low-frequency LFP oscillations that are synchronized with those in primary somatosensory cortex and motor areas [11][12][13][14]. Low-frequency cerebellar oscillations have been recorded in the granule cell layer (GCL) of awake and alert rodents (7)(8) and primates (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) [12,[15][16][17], and are present both at rest and during preparation for movement [12,14,[16][17][18]. In addition, single and multi-unit firing activity within the GCL is phase-locked with GCL oscillations [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…They found that entrainment of the low-frequency component increased phaseamplitude-coupling (PAC), where gamma power became preferentially locked to the 'trough' or 'down-phase' of the alpha oscillation, while gamma-band entrainment enhanced amplitude-envelope correlations (AECs) and reduced alpha power (Helfrich et al, 2016). …”
mentioning
confidence: 99%